First report of rhizoctonia solani kuhn. Isolated from parthenium weed (Parthenium hysterophorus L.) in Malaysia - S. M. R., Karim; Naher, Laila; M. Z., Norhafizah; Kayat, Fatimah; Sarip, Nabilah (UPM Press, 2018)
Fungal pathogens are useful in biocontrol of parthenium weed (Parthenium hysterophorus L.) for efficient weed management. Although parthenium is a major problem in Malaysia, no initiative for developing biocontrol method has been taken yet. Therefore, a field study was conducted at Kg. Durian Tunggal, Melaka (Latitude: 2020'55"N, Longitude:102017'33'' E), Malaysia in August 2017 to isolate disease-causing pathogens of parthenium weed. Diseased parthenium leaves with symptoms of yellowish-brown leaf blight and the parthenium stem with reddish-brown cankers on the basal part were collected and examined after they were cultured in potato dextrose agar (PDA) medium. Isolated fungus was identified based on morphological and microscopy analyses. Two isolates, UMKRSPL1 and UMKRSPS1, were isolated qualitatively from the infected leaves and stem respectively, that yielded dark-brown colonies of sclerotia on PDA. Under the microscopic study, the mycelia with multi-nucleolus hyphal cells were noted, which were septate and hyaline. The hyphae branched at right and acute angles to the primary hypha. There was no conidium. Pathogenicity of the fungus proved to cause similar symptoms on new, fresh parthenium leaf. Based on cultural and morphological characteristics, the pathogen was identified as Rhizoctonia solani Kuhn. There is no published study on R. solani isolated from P. hysterophorus in Malaysia. This is the first research on the species found on parthenium weed in the country. The identification of pathogens from parthenium.